Informational cascades and technology adoption: Evidence from Greek and German organic growers - Chatzimichael, Konstantinos; Genius, Margarita; Tzouvelekas, Vangelis M. (My University, 2014)
The present study aims to empirically analyze the effect of social interactions and conversion subsidies on the adoption rates of organic farming practices in two samples of olive and cereal growers in Greece and Germany, respectively. To this end we construct two alternative indicators to capture informational cascades created in rural areas. The first indicator is based on demographic characteristics while the other one on profitability considerations since farmers are likely to imitate the behavior of more successful farmers. Building upon the theoretical findings of Foster and Rosenweig (1995), Munshi (2004), Bandiera and Rasul (2006) and Weber (2012), we find that informational cascades are indeed important in revising farmers' perceptions and adoption behavior in both rural areas of Europe. Our results show that conversion subsidies can enhance social network effects internalizing informational externalities even in areas where adoption rates are considerable. This finding is independent of the crop and the country under consideration underlying the importance of informational cascades for technology adoption.
Keywords: Conversion subsidies; Germany; Greece; Informational externalities; Organic farming adoption